Beispiel Nr: 08
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ 8x -3y =10\\ 12x -5y = 24 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} I \qquad 8 x -3 y =10\\ II \qquad 12 x -5 y = 24 \\ \text{I nach x auflösen}\\ 8 x -3 y =10 \\ 8 x -3 y =10 \qquad /+3 y\\ 8 x =10 +3 y \qquad /:8 \\ x =1\frac{1}{4} +\frac{3}{8} y \\ \text{I in II}\\ 12 (1\frac{1}{4} +\frac{3}{8} y ) + -5 y = 24 \\ 15 +4\frac{1}{2} y -5 y = 24 \qquad / -15 \\ +4\frac{1}{2} y -5 y = 24 -15 \\ -\frac{1}{2} y = 9 \qquad /:\left(-\frac{1}{2}\right) \\ y = \frac{9}{-\frac{1}{2}} \\ y=-18 \\ x =1\frac{1}{4} +\frac{3}{8} y \\ x =1\frac{1}{4} +\frac{3}{8} \cdot \left(-18\right) \\ x=-5\frac{1}{2} \\ L=\{-5\frac{1}{2}/-18\} \end{array} & \begin{array}{l} I \qquad 8 x -3 y =10\\ II \qquad 12 x -5 y = 24 \\ \text{I nach y auflösen}\\ 8 x -3 y =10 \\ 8 x -3 y =10 \qquad /-8 x\\ -3 y =10 -8x \qquad /:\left(-3\right) \\ y =-3\frac{1}{3} +2\frac{2}{3}x \\ \text{I in II}\\ 12x + -5(-3\frac{1}{3} +2\frac{2}{3} x ) = 24 \\ 16\frac{2}{3} -13\frac{1}{3} x -5 x = 24 \qquad / -16\frac{2}{3} \\ -13\frac{1}{3} x -5 x = 24 -16\frac{2}{3} \\ -1\frac{1}{3} x = 7\frac{1}{3} \qquad /:\left(-1\frac{1}{3}\right) \\ x = \frac{7\frac{1}{3}}{-1\frac{1}{3}} \\ x=-5\frac{1}{2} \\ y =-3\frac{1}{3} +2\frac{2}{3} x \\ y =-3\frac{1}{3} +2\frac{2}{3} \cdot \left(-5\frac{1}{2}\right) \\ y=-18 \\ L=\{-5\frac{1}{2}/-18\} \end{array} \end{array} $